2005
DOI: 10.1065/espr2005.06.270
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Fluctuation in Heavy Metal Pollution in Iran´s Siahroud River - A Preliminary Study (7 pp)

Abstract: Preventive measures need to be undertaken in the land-use systems and watersheds of the Siahroud River to reduce the pollution levels of Pb, Cd, Mn and Fe.Cd, Mn and Fe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Heavy metal contamination of sediments can critically degrade aquatic systems (Charkhabi et al 2005). Their release from the sediment can make them enter the aquatic ecosystems and bring about severe problems (Mohammed and Markert 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal contamination of sediments can critically degrade aquatic systems (Charkhabi et al 2005). Their release from the sediment can make them enter the aquatic ecosystems and bring about severe problems (Mohammed and Markert 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The 720-km-long Sefid Rud River discharges into the nearshore area of sites 5 and 6 and this river is contaminated with agricultural, food processing, pulp and paper, industrial and urban wastes from various sources located in its 67,000 km 2 drainage basin. The pollution of waterways in Iran with heavy metals from a variety of sources was discussed by Diagomanolin et al (2004) and Charkhabi et al (2005). Significant findings on heavy metal contamination in the Karoon River drainage basin was presented by Diagomanolin et al (2004), while heavy metal pollution of the Siahroud River was reported by Charkhabi et al (2005).…”
Section: Discussionmentioning
confidence: 97%
“…The accumulation of metal contamination in sediments can pose serious environmental problems and can critically degrade aquatic systems (Tessier and Campbell 1987;Charkhabi et al 2005;Lien et al 2005). When environmental conditions change (pH cation exchange capacity, nutrient status, redox potential, etc.…”
Section: Introductionmentioning
confidence: 98%